CORRELATION STUDIES AMONG YIELD RELATED TRAITS FOR SEED YIELD IN SUNFLOWER (HELIANTHUS ANNUUS L.) UNDER CHARCOAL ROT STRESS CONDITIONS - Jalil, Sanaullah; Sadaqat, Hafeez Ahmed; Tahir, Hammad Nadeem (European Scientific Journal, ESJ, 2014)
Twenty four different accessions of sunflower evaluated for their resistance to charcoal rot caused by Macrophomina phaseolina under artificially field conditions. The accessions were planted according to factorial experiment in randomized complete block design with three treatments within three replications. Mean squares from analysis of variance revealed significant differences among all accessions evaluated for yield related traits and resistance to charcoal rot disease. Genotypic and phenotypic correlation coefficients in each accessions of sunflower derived from random mated sunflower UAF population. The estimates of genetic correlation coefficients were found greater in value than the phenotypic correlation coefficients for all the indicated traits for all accessions of sunflower. Seed yield per plant was positively and significant correlated with all the traits studied i.e. head diameter, number of achenes per head, head weight, 100-seed weight and oil contents at both genetical and phenotypical levels within all three treatments. Hence selection of these characters would contribute for the improvement of the seed yield per plant.